Analysis of risk factors for adverse events associated with cardiogenic syncope due to coronary artery disease in the elderly - Yangyang Liang; Xinping Li; Shuguang Chen; Qiaoying Cha; LiYa Yang (BMC Cardiovascular Disorders)
Abstract Objective To analyze risk factors for adverse events associated with syncope due to coronary artery disease (CAD) in the elderly. Methods Two hundred eight patients with CAD who were hospitalized for cardiogenic syncope in our hospital from September 2022 to September 2023 were included in this study. Based on the follow-up results, 208 patients with cardiogenic syncope due to geriatric coronary artery disease were classified into the no-adverse group (n = 171), and the adverse group (n = 37), and the risk factors for the occurrence of adverse events in cardiogenic syncope in both groups were analyzed. Results The age differences, history of heart failure, cardiac troponin I (hs-TnT) level, N-terminal B-type natriuretic peptide proteins (NT-proBNP) level, heart rate, left ventricular ejection fraction (LVEF), and QTC abnormality between the two groups were statistically significant (P < 0.05). The COX multifactorial regression analysis revealed that hs-TnT, NT-proBNP, QTC abnormality prolongation and LVEF were all identified as risk factors for poor prognosis in elderly CAD patients (P < 0.05). proBNP, abnormal prolongation of QTC, and LVEF were identified as risk factors for cardiogenic syncope in elderly CAD patients, leading to a poor prognosis (P < 0.05). ROC curve analysis demonstrated that combining hs-TnT, NT-proBNP, QTC, and LVEF tests resulted in higher diagnostic accuracy than a single test alone, significantly improving the diagnostic accuracy (P < 0.05). Conclusion High hs-TnT and NT-proBNP levels, abnormally prolonged QTC, and LVEF > 50% are risk factors for cardiogenic syncope leading to adverse events in elderly CAD patients. The clinical Trial Number of this study is CLTR202356423, and it was registered in 2023.